2006
DOI: 10.1074/jbc.m600214200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch Modulates the Promoter Activity of the Profibrotic Factor CCN2 through Increased Actin Polymerization and NF-κB Activation

Abstract: The connective tissue growth factor known as CCN2 is an inducible, profibrotic molecule that becomes aberrantly expressed in mechanical overload-bearing tissues. In this study, we found that CCN2 gene expression is rapidly induced in cyclically stretched bladder smooth muscle cells (SMCs) in vitro and in the detrusor muscle of a mechanically overloaded bladder in a rat model of experimental urethral obstruction. The activity of CCN2 promoter constructs, transiently transfected into cultured SMCs, was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 67 publications
2
59
1
Order By: Relevance
“…Our results are in agreement with studies showing CCN2 suppression by inflammatory cytokines in other cell types, including chondrocytes, where prostaglandin E 2 , IL-1␤, and TNF-␣ are inhibitory (27)(28)(29)(30). Unlike in NP cells, some studies have reported the involvement of NF-B signaling in the induction of CCN2 in response to LPS, mechanical stretch, and hepatocyte growth factor (25,31,32). Thus, our results suggest that although p65-mediated gene repression is less common, it is context-and cell type-dependent (33).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are in agreement with studies showing CCN2 suppression by inflammatory cytokines in other cell types, including chondrocytes, where prostaglandin E 2 , IL-1␤, and TNF-␣ are inhibitory (27)(28)(29)(30). Unlike in NP cells, some studies have reported the involvement of NF-B signaling in the induction of CCN2 in response to LPS, mechanical stretch, and hepatocyte growth factor (25,31,32). Thus, our results suggest that although p65-mediated gene repression is less common, it is context-and cell type-dependent (33).…”
Section: Discussionsupporting
confidence: 82%
“…There are two conserved NF-B binding sites at Ϫ93/Ϫ86 and Ϫ546/Ϫ537 bp on the human CCN2 promoter (24,25). We used the Multiz alignment in the UCSC Genome Browser to compare conservation of these sites between species.…”
Section: Pro-inflammatory Cytokines Il-1␤ and Tnf-␣ Decreasementioning
confidence: 99%
“…The CTGF luciferase reporter plasmid pCTGF (Ϫ1999/ϩ36)-luc (30), which is based on the backbone of vector pGL3-basic (Promega), was a gift from Dr. B. Chaqour.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin Immunoprecipitation (ChIP) Assay-ChIP was performed as described previously with modifications allowing for a quantitative analysis of protein-DNA interaction (9). DNA-protein complexes were fixed by directly adding formaldehyde (1%) to freshly dissected retinas or cultured cells.…”
Section: Methodsmentioning
confidence: 99%